2014
DOI: 10.1519/jsc.0b013e31829797b4
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Protocol for Patellar Tendinopathy Applied Among 16- to 19-Year Old Volleyball Players

Abstract: The aim of the study was to investigate the efficacy of rehabilitation protocol applied during competitive period for the treatment of patellar tendinopathy. A total of 28 male volleyball players were divided into two groups. Fifteen from experimental group (E) and 13 from control group (C) fulfilled the same tests 3 times: before the training program started (first measurement), after 12 weeks (second measurement) and after 24 weeks (third measurement). The above-mentioned protocol included the following: USG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 51 publications
0
25
3
2
Order By: Relevance
“…Only one 11 of the six studies including mixed populations of adolescents and adults was included in the data synthesis (details of exclusion outlined below). This study by Biernat et al compared the effect of usual care to eccentric exercises in male adolescents on patient-recorded outcomes (VISA-P questionnaire).…”
Section: Resultsmentioning
confidence: 99%
“…Only one 11 of the six studies including mixed populations of adolescents and adults was included in the data synthesis (details of exclusion outlined below). This study by Biernat et al compared the effect of usual care to eccentric exercises in male adolescents on patient-recorded outcomes (VISA-P questionnaire).…”
Section: Resultsmentioning
confidence: 99%
“…13,14 Biernat et al used ultrasonography to examine the structural changes of the patellar tendon during a rehabilitation protocol that consisted of eccentric exercise in competitive volleyball players and found that eccentric exercise can be effective when combined with functional exercises in treating patellar tendonapathy. 15 Although studies have been conducted using diagnostic ultrasound to evaluate structural changes in various tendons and muscle-tendon units (MTUs), these studies have not compared different types of exercise and/or stretching. 11,[16][17][18][19][20] An increase in knowledge of structural changes is needed to aid healthcare professionals in rehabilitation of patients.…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 , 14 , 15 Functional rehabilitation consists of analgesic and anti-inflammatory measures in association with mechanical therapy consisting of eccentric strengthening and specific stretching. 16 , 17 , 18 …”
Section: Introductionmentioning
confidence: 99%